Analisa dan Implementasi Controller untuk Device PTMP Menggunakan Cloud UISP pada PT. Bandar Abadi` - Haeruddin Haeruddin; Kelvin Kelvin (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
A wireless network is a network that uses electromagnetic waves as the transmission medium. Wireless networks have advantages over wired transmission media such as ease of installation, expansion, and lower costs. In wireless networks there are several topologies that are commonly used, namely Point to Point and Point to Multipoint. This topology uses at least 2 devices to transmit data. This in turn makes it difficult to manage devices because of the large number of devices needed. To overcome this issue, the author uses a Controller, namely Cloud UISP to manage all existing PTMP devices. With this device, it enables IT to detect, register and configure PTMP devices all in one place. In designing this network the author uses Network Development Life Cycle (NDLC) method. The results of this implementation make it easier for IT to manage all Ubiquiti PTMP devices in the company.